Survey of Basic Basketball Techniques Skills in State Senior High School Basketball Athletes 4 Pasuruan City - Prasetya, Mukhammad Rivanda Dinata; Widiawati, Prisca (Indonesian Journal of Sport Management, 2024)
This research is motivated by the decline in achievement in State High School Basketball Athletes 4 Pasuruan City in the last 3 years. This study aims to determine the level of basic basketball technical skills in basketball athletes of SMA Negeri 4 Pasuruan City. This research is included in a quantitative descriptive study with the subject being athletes of SMA Negeri 4 Pasuruan City totaling 22 people. The research sample used the total sampling method. The method used in this study is a survey method with data collection techniques using the Johnson Basketball Test instrument consisting of Passing and throwing the ball at the target that has been made. 2. Dribble, passing through obstacles with zig-zag counting time until crossing the finish line. 3. Shooting, shooting the ball close to the ring, and counting the number of balls that enter. The results of this study were then converted into T scores. For each passing category there are 9 with an average of 16.86 athletes in the good category, dribbling there are 7 athletes with an average of 8.011 in the sufficient category, shooting there are 8 athletes with an average of 20.40 in the good category. Based on the results of the study, it can be concluded that the overall basic techniques of passing, dribbling, and shooting which are converted into T score values are included in the moderate category.